International law and religion: historical and contemporary perspectives - Koskenniemi, Martti; García-Salmones, Mónica; Amorosa, Paolo (The history and theory of international law, 2017)
This collective volume brings together contributions by academics in various fields of law and the humanities, in order to tackle the complex interactions between international law and religion. The originality and the variety of approaches makes this work a must-have for academics planning to approach the topic in the future